Corazonin Neurons Contribute to Dimorphic Ethanol Sedation Sensitivity in Drosophila melanogaster - Oyeyinka, Adeola; Kansal, Mehul; O’Sullivan, Sean M.; Gualtieri, Claudia; Smith, Zachary M.; Vonhoff, Fernando J. (Frontiers in Neural Circuits, 2022)
Exposure to alcohol has multiple effects on nervous system function, and organisms have evolved mechanisms to optimally respond to the presence of ethanol. Sex differences in ethanol-induced behaviors have been observed in several organisms, ranging from humans to fruit flies. However, the molecular mechanisms underlying the dimorphic regulation of ethanol-induced behaviors remain incompletely understood. Here, we observed sex differences in ethanol sedation sensitivity in DGRP lines of Drosophila melanogaster compared to the absence of dimorphism in standard laboratory wildtype and control lines. However, in dose response experiments, we were able to unmask dimorphic responses for the control mutant line w1118 by lowering the testing ethanol concentration. Notably, feminization of the small population of corazonin neurons in males was sufficient to induce female-like sedation sensitivity. We also tested the role of the transcription factor apontic based on its known expression in Crz neurons and its regulation of sedation responses. Interestingly, loss of function apontic mutations increased sedation times in both males and females as compared to controls. No significant difference between male and female apontic mutants was observed, suggesting a possible role of apontic in the regulation of dimorphic ethanol-induced responses. Thus, our results shed light into the mechanisms regulating sex-differences in ethanol-induced behaviors at the cellular and molecular level, suggesting that the genetic sex in a small neuronal population plays an important role in modulating sex differences in behavioral responses to ethanol.